Marie - Lepscky, Ibi.; Cardoni, Paolo (Barcelona : Ediciones Destino, 1990)
A biography focusing on Marie Curie's childhood, during which she exhibited her sensitivity, intelligence, and scientific curiosity.
Keywords: Curie, Marie, -- 1867-1934 -- Juvenile literature; Chemists, -- France -- Biography -- Juvenile literature